Pengaruh EVA, MVA, dan REVA Terhadap Kinerja Keuangan Pada Perusahaan Farmasi di BEI - Andrinaldo, Arisky; Apandi, Apandi; Fahdillah, Lidya (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
The purpose of this study was to determine the effect of Economic Value Added (EVA), Market Value Added (MVA), and Refined Economic Value Added (REVA) on financial performance in pharmaceutical companies listed on the Indonesia Stock Exchange (IDX). The independent variables used are Economic Value Added (EVA), Market Value Added (MVA), and Refined Economic Value Added (REVA) the dependent variable used is financial performance. The population in this study were pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) in the period 2018-2022. The sampling method used was the purposive sampling method with a sample of 9 companies during the 5-year observation period. The analysis method of this study uses Quantitative. The results of this study indicate that Economic Value Added (EVA) partially has no significant effect on Financial Performance in pharmaceutical companies listed on the IDX. Market Value Added (MVA) does not have a significant effect on Financial Performance in pharmaceutical companies listed on the IDX. While REVA has a significant effect on Financial Performance. While EVA, MVA, and REVA simultaneously have a significant effect on Financial Performance